A Prospective Study to Assess Patients' Understanding and Retention of Postoperative Instructions following a Fixed Partial Denture, Using Different Information Delivery Techniques - Adawi, Hafiz; Jain, Saurabh; Hakami, Aeshah H.; Mtwam, Naseem A.; Koriri, Almaha Y. A.; Adawi, Abdulaziz A. A. (European Journal of Dentistry, 2022)
Objective This study was aimed to evaluate the effect of using different modes of at-home maintenance information delivery on patients' understanding and the level of information retention.Materials and Methods Sixty patients were asked to answer a questionnaire while undergoing mouth preparations for receiving a fixed partial denture. The questionnaire includes questions related to at-home maintenance procedures and recall visits. After finishing the first questionnaire, these patients were randomly assigned into three groups, and each group was given education about at-home maintenance procedures and recall visits by different means. Group 1 participants were educated by giving live demonstrations. Group 2 participants were shown a prerecorded video, whereas group 3 participants were given written instructions. All Participants were recalled after 1 week of the last visit and were asked to fill out the same questionnaire.Statistical Ananlysis Collected data were tabulated in a Microsoft Excel Spreadsheet and were analyzed using the Chi-square test, one-way ANOVA, paired t-test, and post hoc Bonferroni test. A p-Value < 0.05 was regarded as statistically significant for all the analyses.Results Group 1 showed greatest information retention as compared with groups 2 and 3 (p = 0.045). There was significant difference in the knowledge of group 1 as compared with groups 2 (p = 0.020) and 3 (p = 0.048).Conclusion The mode of delivering postoperative instructions after fixed partial denture treatment does have an effect on the patient understanding level and information retention. Patients who were given live demonstrations showed the best results compared with video recordings and written leaflets.
Keywords: at-home maintenance instructions; fixed partial denture; instruction delivering modes; patient education; patient understanding